In a service-oriented architecture, who will do the cooking? understanding management trends in the new age of service-oriented architectures. - Lipton, Paul
The acclaimed essayist and novelist Nora Ephron once said, "What my mother believed about cooking is that if you worked hard and prospered, someone else would do it for you." Nothing could better capture the spirit of service-oriented architectures (SOAs) than this statement from a person who clearly does not consider cooking a core competency. Translated to human terms, an SOA can help make sure that the right person is doing the cooking at the right time.